High-resolution stable oxygen and carbon isotope data from IODP Site 342-U1403, Newfoundland Margin - Alexa Fischer; Sietske J Batenburg; André Bahr; Silke Voigt; Anne Rheinberger; Sarah Schmickal; Silvia Rheinberger; Markus Greule; Stefan Rheinberger; Oliver Friedrich (PANGAEA, 2025)
This dataset lists the results of stable oxygen and carbon isotope measurements (in extperthousand VPDB) from International Ocean Discovery Program (IODP) Site U1403 off Newfoundland (~40°N, 51°W; 4944 m water depth, Expedition 342, NW Atlantic Ocean). Stable isotope analysis were carried out on specimens of N. truempyi. Stable isotopes were analyzed using a ThermoFinnigan MAT253Plus gas source mass spectrometer equipped with a Thermo Fisher Scientific KIEL IV carbonate device. Values are reported relative to the VPDB through the analysis of an in-house standard (Solnhofen limestone) calibrated to IAEA-603.